If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11h + 21 = -8h + -36 Reorder the terms: 21 + 11h = -8h + -36 Reorder the terms: 21 + 11h = -36 + -8h Solving 21 + 11h = -36 + -8h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '8h' to each side of the equation. 21 + 11h + 8h = -36 + -8h + 8h Combine like terms: 11h + 8h = 19h 21 + 19h = -36 + -8h + 8h Combine like terms: -8h + 8h = 0 21 + 19h = -36 + 0 21 + 19h = -36 Add '-21' to each side of the equation. 21 + -21 + 19h = -36 + -21 Combine like terms: 21 + -21 = 0 0 + 19h = -36 + -21 19h = -36 + -21 Combine like terms: -36 + -21 = -57 19h = -57 Divide each side by '19'. h = -3 Simplifying h = -3
| -6z=-14 | | 5x=7+11 | | 23z-29=17z+13 | | 5x^2-40x+35=0 | | 3x=0.5x^2+2.5 | | 19f=-12f+56 | | 4x+2(3-2x)=6 | | 37-18+8w=-43 | | 106-7x=20x+22 | | 7m-5=-12 | | 70-5x=13x+22 | | 5-8x=37-15x | | -x=-12 | | 4(3x+2)=68 | | 8m+3m= | | -74-7x=8x+16 | | 3x-10(x+2)=1-7x | | 5(x-4)=3(x+2) | | 10-10x=200-45x | | 2x^2-8*x-90=0 | | -35-5x=5-9x | | 9x-27=9(x+2)+9 | | (-3y)x(4z)= | | 5x=3y | | 36*x^2-25=0 | | 12x+50y=5 | | 9-5n=16 | | -33-8x=10x-21 | | 9x+10=46 | | 2.4m-3+3.8=-8.2 | | 6+k=-k+2-9 | | 12x+30=4x+158 |